Continuously relapsing (for two years) course of diarrheal variant of IBS (Clinical case) - Ye. A. Poluektova; S. Yu. Kuchumova; A. A. Kurbatova; A. A. Sheptulin; O. S. Shifrin; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of the publication. By the example of clinical case to show modern algorithm of diagnostics and choice of pathogenically proved treatment for patient with continuously relapsing course of irritable bowel syndrome (IBS).Key points. Patient S., 20 years, has addressed in clinic with symptoms of boring pain in the lower regions of the abdomen, aggravating after meal and decreasing after defecation, increase of stool frequency up to 6 times day, mainly in the morning time, general weakness. Symptoms developed about two years ago after the intake of unsound food nausea, vomiting by taken food, abdominal pain, frequent stool with admixture of mucus appeared. Patient had no nausea and vomiting the next day, however the abdominal pain and unstable stool persisted for a long time. The patient was repeatedly examined, but according to carried out investigation no significant changes were revealed. Antispasmodics of various groups, enzyme and antisecretory agents in this relation were prescribed to him without any noteworthy effect for two years prior to admission to Vasilenko Clinic of internal diseases propedeutics, gastroenterology and hepatology. In the clinic differential diagnosis between organic diseases of gastro-intestinal tract was carried out (erosive-ulcerative lesion of the upper parts of GIT, celiac disease, inflammatory bowel diseases), functional gastro-intestinal disorder, thyroid gland hyperfunction). According to symptoms, data of past history and carried out investigation clinical diagnosis was made: postinfectious irritable bowel syndrome, diarrhea-prevalent variant. Prescribed treatment included dioctaedric smectite, probiotic and antipsychotic drug, which had led to complete relief of all symptoms.Conclusion. Careful taking past history and carrying out detailed laboratory and instrumental tool investigation allowed to establish clinical diagnosis in the patient, and pathogenicly proven treatment promoted achievement of disease remission.